Novel Aspects of Nanofibers - Lin, Tong (IntechOpen, 2018)
This book is a supplement of the previous book Nanofibers: Production, Properties and Functional Applications (published by InTech in 2011). It reports on novel methods of fabricating nanofibers, nanofiber yarns, and collagen nanofibers; functionalities of photochromic nanofibers, bead-on-string nanofibers, and bio-regeneration nanofibers; as well as piezoelectric nanoparticle-reinforced nanofibers. I deeply appreciate the authors' great contributions to nanofiber discipline.